2018
DOI: 10.1016/j.celrep.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Psychedelics Promote Structural and Functional Neural Plasticity

Abstract: SUMMARYAtrophy of neurons in the prefrontal cortex (PFC) plays a key role in the pathophysiology of depression and related disorders. The ability to promote both structural and functional plasticity in the PFC has been hypothesized to underlie the fast-acting antidepressant properties of the dissociative anesthetic ketamine. Here, we report that, like ketamine, serotonergic psychedelics are capable of robustly increasing neuritogenesis and/or spinogenesis both in vitro and in vivo. These changes in neuronal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
795
1
22

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 735 publications
(867 citation statements)
references
References 110 publications
49
795
1
22
Order By: Relevance
“…We characterized these mutants for various cocaine-induced behaviors such as acute response to cocaine, locomotor sensitization following non-contingent repeated cocaine administration and cocaine selfadministration, to conclude that Tmod2 KO have reduced cocaine-induced locomotor sensitization and are resilient to the reinforcing effects of cocaine. Structural and functional plasticity of synapses are the fundamental mechanisms that underlie addiction even though the role of actin in this process remains controversial 2,11,30,97 . Acute or chronic cocaine exposure, as well as abstinence, facilitates dendritic spine outgrowth and spine density in reward-related brain regions such as prefrontal cortex and nucleus accumbens 31,32,92,98,99 .…”
Section: Discussionmentioning
confidence: 99%
“…We characterized these mutants for various cocaine-induced behaviors such as acute response to cocaine, locomotor sensitization following non-contingent repeated cocaine administration and cocaine selfadministration, to conclude that Tmod2 KO have reduced cocaine-induced locomotor sensitization and are resilient to the reinforcing effects of cocaine. Structural and functional plasticity of synapses are the fundamental mechanisms that underlie addiction even though the role of actin in this process remains controversial 2,11,30,97 . Acute or chronic cocaine exposure, as well as abstinence, facilitates dendritic spine outgrowth and spine density in reward-related brain regions such as prefrontal cortex and nucleus accumbens 31,32,92,98,99 .…”
Section: Discussionmentioning
confidence: 99%
“…Subanesthetic ketamine and flurothyl (a volatile convulsant analogous to ECT) produce very similar EEG effects after the acute pharmacological effects on cortical excitation fade (Kohtala et al 2018). The exact adaptive mechanism that is induced in response to N 2 O exposure (and other rapid-acting antidepressants) (Autry et al 2011;Ly et al 2018) responsible for the facilitation of TrkB signaling upon drug withdrawal (Fig. 3) remains under intense study in my lab.…”
Section: Differential Effects Of Electroconvulsive Shock and Anesthesmentioning
confidence: 98%
“…A recent study showed that psychedelics increase dendritic arbor complexity, promote dendritic spine growth, and stimulate synapse formation. 3 Psychedelics have been shown to decrease activity in the DMN while simultaneously promoting interconnectivity of numerous other brain regions. Neuroimaging studies have also found that these functional changes observed while under the effects of psychedelics are analogous to meditation.…”
Section: Symposium IIImentioning
confidence: 99%